ANALYSIS OF SALMONELLA SP CONTENT IN RAW AND HALF COOKED EGGS IN ULEE KARENG SUB-DISTRICT KOTA BANDA ACEH IN 2023 - Seni, Wildan; Safriyani, Susi; Hidayatullah, Mhd. Hidayatullah (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
Analysis of Salmonella sp content in raw and half-cooked eggs in Solong coffee shops, Ulee Kareng sub-district, Kota Banda Aceh in 2023. Eggs in half-cooked food are processed by boiling an egg for approximately 5 minutes so that high protein is obtained from the egg. Eggs can contain dangerous food bacteria called Salmonella sp. The aim of this research is to find out about the analysis of Salmonella sp. This half-boiled egg food is sold in Solong coffee shops, Ulee Kareng sub-district, Kota Banda Aceh. The results of the research showed that the raw egg samples were negative for containing Salmonella sp bacteria, while the half-cooked egg samples were positive for containing Salmonella sp bacteria. The content of Salmonella sp bacteria in food is expected to meet standards referring to SNI 01-6366-2000, namely negative or zero (0). The conclusion of this study shows that the bacterial content in food through existing health processing does not meet the requirements because eggs contain Salmonella sp bacteria. The previously brewed bacteria still contained bacteria after Salmonella sp. Eggs containing bacteria are thought to be caused by long storage and processing methods that do not meet standards. It is hoped that there will be a need for supervision and education to parent traders by the regional government regarding the importance of processing egg food and increasing efforts to organize food so that the food received by eggs meets consumer health requirements.